Excitation-inhibition of stomach smooth muscles by the nano-sized titanium dioxide materials - Tsymbalyuk О. V.; Naumenko А. М.; Nyporko, A.Yu.; Davidovska Т. L.; Skryshevsky, V. A. (Reports of the National Academy of Sciences of Ukraine, 2015)
The aim of our work consisted in the investigation of the effects of TiO2 nanoparticles (average size of 21 ± 5 nm) on the contractile activity of circular smooth muscles from rat's stomach. The cumulative increase in the concentration of TiO2 (10−6–10−3 mg/ml) is accompanied by a dose-dependent inhibition of spontaneous contractions. When using TiO2 concentrations 10−3, 2.5·10−2, and 5·10−2 mg/ml, the significant increase, of acetylcholine- and K+-induced contractions are observed. The activation of acetylcholine-induced contractions is essentially inhibited by D-600. Vice versa, the atropine presence didn't eliminate the TiO2-stimulated activation of high- K+-induced contractions. Nanoparticles didn't affect the contractions caused by the release of Ca2+ from sarcoplasmic reticulum, but their effects are essentially eliminated via the previous inhibition of the mitochondria function by sodium azide.